COLLECTION OF A REFERENCE EVENT SET FOR REGIONAL AND TELESEISMIC LOCATION CALIBRATION - Bondár I.; Yang X.; Kirichenko V.; Israelsson H.; McLaughlin K.; Engdahl E.R.; Ghalib H.A.A.; Wagner R.; Gupta I.; Hofstetter A.; Ekström G.; Bergman E. (My University, 2004)
A three-year consortium project, with members of Science Applications International Corp., University of Colorado at Boulder, Harvard University, Multimax Inc., Geophysical Institute of Israel, Western Services, and University of California at San Diego, was initiated in 2000 to improve locations and reduce uncertainties in the Middle East, North Africa, Europe, and Western Eurasia. The consortium developed high-resolution three-dimensional models of the Earth's mantle to generate accurate travel-time predictions for regional and teleseismic P phases. Since the approach was purely model-based, a large set of high-quality reference events was needed to validate the model predictions. The consortium has spent considerable effort to collect, vet, and validate reference events located with 5-km accuracy or better by local networks and “promoted” reference events located with an accuracy of 7 km or better by application of multiple-event location techniques. Consortium members built an extensive network of contacts to solicit candidate reference events from local, regional, and national network operators. Strict methodologies were developed to identify candidate reference events in earthquake bulletins, and to validate and quality control the selected candidate reference events. The outcome of the consortium effort was a quality-controlled reference event list with nearly 2000 events and over 200,000 arrivals. The Reference Event List is provided as an electronic supplement to this article.